Formar para diferenciar professores do século XXI: explicitando o (im)previsível em Licenciaturas em Ciências Biológicas - PINHEIRO, Sheila Costa Vilhena (Universidade Federal do Pará, 2017)
The present study aimed a qualitative narrative research approach in order to understand teachers and student teachers‟ ideas and perceptions on theoretical methodological and epistemological aspects which are considered as indicators both scientific and pedagogical for XXI century differentiation on the territory of a dual Degree in Biological Sciences. The locus of the research was a federal public university in the State of Para where such duality is formed by two interfaces located in the training methods of „facing‟ and „distance teaching‟ which have education science teachers as an axis of intersection. The „facing teaching‟ is centered at classroom in Belem city, and the interface 'distance teaching' is offered in decentralized municipalities poles called Maraba, Capanema, Oriximina and Parauapebas. Faced with the challenge of understanding the complexity of those diverse teaching contexts and their visual boundaries at present, I maintain as parameters to differentiate both scientific and pedagogical training of science teachers in the XXI century some issues as diversity, flexibility and innovation, theory and methodological ideas, as well as propositions and teaching practices in transformation. There were some differentiation criteria for selection of research subjects, therefore, I could select 10 students (5 and 5 concerned „facing‟ and „distance teaching‟) coming from the high level of activity during reflexive manifestations of a discipline of teaching in, in which the researcher was also forming, and by his turn 07 formers (3 working in „facing‟, 3 in the „distance teaching‟ and one working in both) were selected based upon a network system by already educated teachers and also by indications of their own pairs since the differentiation criteria of their performance as a teacher-trainer. The design of the research was configured by an isomorphic treatment object, objectives and subjects, however, the uniqueness of each of the interfaces of facing context and distance prevented the isomorphism in terms of the production of empirical material that required procedural methodological differentiation for each interface. Thus, the empirical production on all teacher trainers held by semi-structured interview lasting on average 50 minutes moreover only trainers interface distance registered by filming six planning meetings and continuing education to focus groups. In relation to the students, the empirical production was made by filming their practices and interactions in a classroom teaching activities, moreover semi-structured interviews lasting on average 50 minutes. The organization is built on empirical search for recurring to issues in the speech of the subjects that shaped flow analytical emphases expressing indicators of differentiation, namely: a) Personal and Professional Values, b) Emerging Conceptions about Teaching and Learning Sciences and, c) Practical Training. Narrative analysis of these flows enabled the ideational explanation of principles of differentiation in teaching science education shared among individuals, which can be expressed in key ideas and openness to change, teacher identity in context, emotional intelligence, love for the students and for their own practice, dialogue with the people and with the world, ethical-political commitment and act between risks and uncertainties. Towards these principles, it is necessary to construct changes in the traditional conceptions of teaching and learning questioning the teaching in different educational levels, surpassing the teaching models that trainers and teachers learned when they were students, building positive quality in teaching science/biology knowledge in association with the improvement of teacher training based on a culture of collaborative development of training practices regarding the positive quality of the teacher training and education science/ biology view to the challenges of the XXI century.